2018
DOI: 10.1534/genetics.118.300689
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Respiratory Chain in Regulating Meiosis Initiation in Saccharomyces cerevisiae

Abstract: 23Meiosis is a specific type of cell division that is essential for sexual reproduction in most

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 52 publications
2
17
0
Order By: Relevance
“…In addition to trehalose and glycogen metabolism, our previous study also identified mitochondrial biomass as an excellent predictor for meiosis (Arguello‐Miranda et al, ). These results were consistent with the essential requirement of functional mitochondria for meiosis (Zhao et al, ). Cells with dysfunctional mitochondria, known as “petite,” or with defects in oxidative ATP production are unable to sporulate (Jambhekar & Amon, ).…”
Section: Introductionsupporting
confidence: 91%
“…In addition to trehalose and glycogen metabolism, our previous study also identified mitochondrial biomass as an excellent predictor for meiosis (Arguello‐Miranda et al, ). These results were consistent with the essential requirement of functional mitochondria for meiosis (Zhao et al, ). Cells with dysfunctional mitochondria, known as “petite,” or with defects in oxidative ATP production are unable to sporulate (Jambhekar & Amon, ).…”
Section: Introductionsupporting
confidence: 91%
“…Sporulation requires respiration 73,74 . Relaxed selection on sporulation may therefore indirectly lower the selection also for respiration, and this could partially account for the worse respiratory growth in domesticated lineages.…”
Section: Discussionmentioning
confidence: 99%
“…A nonautonomous feedback loop requires an extracellular signal, and one candidate signal for the Rim101-Ime1 loop is alkaline pH. For example, sporulating colonies increase the pH of their environment (Hayashi et al 1998; Piccirillo et al 2010; Zhao et al 2018), and alkaline pH is the primary stimulus for the Rim101/AR pathway. To determine whether increased pH drives the Rim101-Ime1 positive-feedback loop, we performed two types of experiments.…”
Section: Resultsmentioning
confidence: 99%